Design of new immobilized lipases for biotransformations in aqueous and organic media - Guimarães, José Renato (2023)
A review of the literature covering research on the immobilization of lipases on hydrophobic supports was performed using systematic mapping (MS) concepts. The MS approach enabled the identification of gaps that led to the development of this thesis. The mineralization of lipases immobilized with metal phosphate was the main focus of the study. This strategy is an alternative to solve the nanoflowers fragility while maintaining some of the mineralization benefits. When mineralization is performed on previously immobilized enzymes, the researcher can select the support based on its mechanical resistance, avoiding the difficulties derived from the management of the small and fragile nanoflowers. Moreover, the mineralization of immobilized enzyme couples the positive effects of enzyme mineralization during nanoflowers production with the benefits of enzyme immobilization in preexisting solids. Several lipases were immobilized on octyl agarose beads via interfacial activation and modified with diverse metal phosphates. It was found that the effects of the metal phosphate modification were clearer and more positive using highly loaded biocatalyst, suggesting that enzyme crowding could facilitate some of the positive effects of enzyme mineralization. The effects depended on the nature of both enzyme and metallic phosphate. The incubation with only sodium phosphate or only metal chloride, as well as the immobilization on previously modified supports which produced significantly reduced effects. The immobilized enzyme mineralization cannot produce a tridimensional nanoflower, as the enzymes will be located on a flat planar surface, but the results suggest that the positive effects of the building of nanoflowers may be, at least partially, achieved using this solid-phase strategy. However, we cannot talk of nanoflowers, as these tridimensional structures will never be achieved. The study was later extended to the use of diverse commercial biocatalysts and Thermomyces lanuginosus lipase (TLL) immobilized on Purolite@ C18. The modifications greatly altered enzyme specificity, increasing the activity versus some substrates while decreasing the activity versus other substrates. Enantiospecificity was also drastically altered after these modifications. Regarding the enzyme stability, no significant positive effects were found; in fact, a decrease in enzyme stability was usually detected. The influence of the immobilization protocol on the effects of mineralization was investigated. The stability, activity and specificity of the biocatalysts were very different, both the differently blocked vinyl sulfone biocatalysts (VS-biocatalysts) and the glutaraldehyde biocatalysts prepared at different pH. The activity, specificity and stability effects of the mineralization strongly depended on the enzyme and on the immobilization protocol. For the same enzyme, a mineralization protocol could be negative, positive or present no effect depending on the enzyme immobilization procedure and substrate. These results highlight the great potential of mineralization of immobilized enzymes to improve their properties, as well as the great interactions that immobilization protocol and mineralization can exhibit. The combination of both methodologies greatly increases the possibilities to find a biocatalyst that can be suitable for a specific process. The mineralization of chemically or physically modified immobilized lipases is also a potent tool to improve enzyme features. The changes caused by chemical modifications with glutaraldehyde, trinitrobenzenesulfonic acid or ethylenediamine and carbodiimide, or physical coating with ionic polymers, such as polyethylenimine and dextran sulfate have, in most cases, negative effects with some substrates and positive with other ones. Furthermore, the same mineralization could present different effects on the enzyme activity, specificity or stability, depending on the previous modification performed on the enzyme, showing that these previous enzyme modifications alter the effects of the mineralization on enzyme features. In this way, the combination of chemical or physical modifications of enzymes before their mineralization increases the range of modification of features that the immobilized enzyme can experienced, enabling to enlarge the biocatalyst library. Eversa@ Transform immobilized on Purolite@ C18 was successfully applied in the esterification of purified fatty acids of the hydrolysis of degummed soybean oil for the synthesis of octyl esters. Furthermore, aiming at the application of biocatalysts in organic reactions, TLL was immobilized on Purolite@ C18 aminated and activated with vinyl sulfone. The use of different blocking agents as reaction end point (using ethylene-diamine, aspartic acid, glycine, and cysteine) greatly altered the biocatalyst functional features (activity, specificity, or stability). Furthermore, the differently blocked VS-biocatalysts showed different performances in the synthesis of fatty acid methyl esters. In general, they showed better affinity for the transesterification of polyunsaturated oils.